생성형 AI 기반 공사비 예산 견적 모델 개발 연구 - 공공청사를 중심으로 - 이찬희; 김한수; Chan-Hee Lee; Han Soo Kim (한국건설관리학회 논문집, 26(3), 2025)
Accurately estimating construction project budgets and setting realistic budgets is a critical concern for project owners. However, the high volatility of market conditions and the complexity of regulations and administrative procedures have made cost estimation increasingly challenging. Generative AI technology is expected to overcome the limitations faced by human estimators and enhance the reliability and efficiency of the budget estimation process. The objective of this study is to develop a construction cost estimating model for public buildings using ChatGPT, a type of generative AI, validate the model through scenario testing, and present key insights and recommendations. This study proposes a method for utilizing generative AI in construction cost estimation and suggests that continuous data updates and iterative learning can further improve the reliability and efficiency of construction cost estimates in the future. 건설 프로젝트에서 공사비 예산을 가능한 한 정확하게 추정하여 현실성 있는 예산을 설정하는 것은 발주자에게 매우 중요한 현안이다. 그러나 변동성 높은 시장 상황과 복잡한 규제 및 행정절차로 인해 공사비 예산 견적의 난이도가 더욱 증가하고 있다. 생성형 AI 기술은 인간 견적자가 직면하는 한계를 극복하고, 예산 추정 과정의 신뢰성과 효율성을 향상하는 데 기여할 것으로 기대되고 있다. 본 연구의 목적은 생성형 AI 중 ChatGPT를 활용하여 공공청사의 공사비 예산 견적 모델을 개발하고, 시나리오 테스트를 통해 검증하며, 주요 교훈과 제안사항을 제시하는 데 있다. 본 연구를 통해 생성형 AI를 공사비 예산 견적에 활용하는 방안을 제시하였으며 향후 지속적인 데이터 추가와 반복 학습을 통해 공사비 예산 견적의 신뢰성 및 효율성을 제고할 수 있다.